Self-assessment of some teacher competencies for working with children with disabilities - Kadum, Sandra; Radetić-Paić, Mirjana (Journal of Education Culture and Society, 2021)
Aim. The aim of this study is to define teacher competencies and some specific differences in self-assessment with regard to the completion of studies according to the new or the old curriculum. Efforts were also made to gain insight into the specific deficiencies of the competencies related to the integrated education and training of children with developmental disabilities. Methodology. The research was conducted on a sample of 212 regular primary school teachers who dealt with children with disabilities in their work. A questionnaire constructed for the purposes of this research was used. Previously, a pilot study was conducted. Participants were divided into two groups. One group of teachers who were educated according to the old program and teachers who were educated according to the new program in the broad context of working with children with disabilities. Results. The obtained results indicate differences between the observed groups and the need for continuous (self) assessments of teachers’ responsibilities to enable students with disabilities to learn and thrive in line with their abilities as well as to find alternative ways to meet their different needs in a wider sense. Also, teachers are aware of the need for continuous training in this area. These findings have contributions in the scientific and practical sense.